The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1991
DOI: 10.1111/j.1365-2044.1991.tb09847.x
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐ocular pressure changes using the laryngeal mask airway and tracheal tube

Abstract: SummaryIntra-ocular pressure was measured before and throughout airway establishment with either the laryngeal mask airway or tracheal tube. Similar measurements were made on removal of either airway and the amount of coughing noted in thejrst minute after removal. There was a significantly smaller increase in intra-ocular pressure ( p < 0.001) using the laryngeal mask airway, both on placement and removal, than with the tracheal tube. Postoperative coughing was significantly reduced using the laryngeal mask a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
43
0
1

Year Published

1993
1993
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 7 publications
2
43
0
1
Order By: Relevance
“…Postoperative hoarseness, sore throat, impairment of swallowing, pain, nausea and vomiting, and coughing are reduced, post-anaesthesia recovery unit length of stay is shortened, and increases in intra-ocular pressure and derangements in cardiovascular and respiratory function are less likely [1][2][3][4][5][6][7][8][9][10][11]. Furthermore, the LMA can be useful in the management of the difficult airway when facemask ventilation is inadequate [12].…”
mentioning
confidence: 99%
“…Postoperative hoarseness, sore throat, impairment of swallowing, pain, nausea and vomiting, and coughing are reduced, post-anaesthesia recovery unit length of stay is shortened, and increases in intra-ocular pressure and derangements in cardiovascular and respiratory function are less likely [1][2][3][4][5][6][7][8][9][10][11]. Furthermore, the LMA can be useful in the management of the difficult airway when facemask ventilation is inadequate [12].…”
mentioning
confidence: 99%
“…A modified laryngeal mask with a flexo-metallic tube was first described in 1990 [14] and is now recognised as a suitable alternative to tracheal intubation in patients undergoing elective eye operations [ 151-usually with controlled ventilation [5-91. The changes in IOP in previous studies have varied with the techniques used. Some authors have shown increases after tracheal intubation [5,9,161 whereas others have shown a reduction [7]. Many authors [5,6,9,161 have shown significantly lower IOPs after insertion of a laryngeal mask compared to tracheal intubation.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have shown increases after tracheal intubation [5,9,161 whereas others have shown a reduction [7]. Many authors [5,6,9,161 have shown significantly lower IOPs after insertion of a laryngeal mask compared to tracheal intubation. Our present results showed a significant reduction in IOP after intubation in both groups compared to baseline.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations